Ventricular Arrhythmias in Patients Undergoing Primary Percutaneous Coronary Intervention (PCI) for ST-Segment Elevation Myocardial Infarction (STEMI) - Qamar Zaman Qaim Khani, Zuhaib Zahoor Soomro, Kanwal Naz, Tahir Hussain Soomro, Asad Aslam Korejo, Fayaz Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of ventricular arrhythmias in patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction (STEMI) at a tertiary care hospital in Karachi, Pakistan. Material and Methods: This descriptive case series study was done at the National Institute of Cardiovascular Disease, Karachi. All patients of either gender having an age between 18 and 70 years of diagnosis with STEMI undergoing primary PCI were included. All the patients were kept under observation for 72 hours in the hospital, and ventricular arrhythmias such as Accelerated Idioventricular Rhythm (AIVR), Frequent PVCs (premature ventricular contractions), Non-Sustained Ventricular Tachycardia, Sustained Ventricular Tachycardia, and Ventricular Fibrillation were recorded. Results: The mean age of the patients was 54.72 ±10.75 years. The majority of the patients, 75.2%, were males and 24.8% were females. The frequency of ventricular arrhythmia was found in 89 (25.9%) of the patients. Among 89 patients with ventricular arrythmia, AIVR was found in 30 (33.71%), frequent PVCs in 18 (20.22%), non-sustained ventricular tachycardia in 23 (25.84%), sustained ventricular tachycardia and ventricular fibrillation in 9 (10.11%) each. Conclusion: As per the study conclusion, the ventricular arrhythmias was observed to be considerably higher among patients undergoing primary PCI for ST-STEMI. Keywords: Ventricular arrhythmias, PCI, ST-segment elevation MI